Development of an antimicrobial dressing for catheter exit site infections in peritoneal dialysis (2024)
At Third P. Solutions, we are committed to advancing healthcare through the development of innovative technological solutions. This project aims to comprehensively identify and analyze the primary need that can be addressed by leveraging the strengths of our team. To achieve this goal, we conducted an extensive information gathering process, including interviews and literature reviews, aiming to identify three critical needs for further development. Within this context, we have delved into the fundamentals of each medical condition, exploring epidemiology, anatomy, physiology, pathophysiology, clinical presentation, and economic impact. Additionally, we have conducted a detailed analysis of the key stakeholders involved in each need, ranging from patients and caregivers to healthcare service providers and funding entities. Finally, we have conducted a comprehensive market analysis to define a clear strategy that guides our research and innovation process. This analysis enables us to identify opportunities and challenges, as well as determine which need aligns most closely with our working methodology. Our findings concluded that the need that best meets most of our acceptance criteria is a way to address tunneled catheter-related infections in peritoneal dialysis patients with a novel medical device that improves infection prevention and treatment outcomes. Therefore, Third P. Solutions developed Biodial, an antimicrobial dressing that treats infections around the catheter exit site, especially the ones caused by Pseudomonas aeruginosa and Staphylococcus aureus.